Legal Protection for Children as Victims of Commercial Sexual Exploitation on Social Media - Bonaraja Purba; Darwin Sinaga; Jeremi Tampubolon; Nico Purba (PT FORMOSA CENDEKIA GLOBAL, 2023)
The government plays a role in protecting all forms of children's rights and providing education about the dangers of sexual exploitation on social media. This study uses the normative legal writing method which refers to the principles, norms, rules of law, court decisions, agreements and doctrines of the technique of collecting legal materials by using the method of literature, legislation related to the type of normative legal research by analyzing each book material. which is used to choose according to the topic of thesis research which will be analyzed systematically and relate it to other legal materials. This study aims to determine the legal protection arrangements for children as victims of commercial sexual exploitation on social media and punishment or deterrent action against perpetrators of commercial sexual exploitation of children on social media. The results of the study reveal that sexual exploitation of children on social media is stated as a violation of what is contained in dealing with the form of protection given to a child as a victim of commercial sexual exploitation behavior on social media. It is a crime for perpetrators of child exploitation by paying one hundred million rupiah with a five-year prison sentence.